Application of a fully integrated photodegradation-detection flow-batch analysis system with an on-line preconcentration step for the determination of metsulfuron methyl in water samples - Acebal, Carolina C; Grünhut, Marcos; Srámková, Ivana; Chocholouš, Petr; Lista, Adriana G; Sklenářová, Hana; Solich, Petr; Band, Beatriz S Fernández (Talanta, 2014)
This work presents the development of a fully automated flow-batch analysis (FBA) system as a new approach for on-line preconcentration, photodegradation and fluorescence detection in a lab-constructed mixing chamber that was designed to perform these processes without sample dispersion. The system positions the mixing chamber into the detection system and varies the instrumental parameters according to the required photodegradation conditions. The developed FBA system is simple and easily coupled with any sample pretreatment without altering the configuration. This FBA system was implemented to photodegrade and determine the fluorescence of the degradation products of metsulfuron methyl (MSM), a naturally non-fluorescent herbicide of the sulfonylurea׳s family. An on-line solid phase extraction (SPE) and clean up procedure using a C18 minicolumn was coupled to the photodegradation-detection mixing chamber (PDMC) that was located in the spectrofluorometer. An enrichment factor of 27 was achieved. Photodegradation conditions have been optimized by considering the influence of the elution solvent on both the formation of the photoproduct and on the fluorescence signal. Under optimal conditions, the calibration for the MSM determination was linear over the range of 1.00-7.20 µg L(-1). The limit of detection (LOD) was 0.28 µg L(-1); the relative standard deviation was 2.0% and the sample throughput for the entire process was 3h(-1). The proposed method was applied to real water samples from the Bahía Blanca׳s agricultural region (Bahía Blanca, Buenos Aires, Argentina). This method obtained satisfactory recoveries with a range of 94.7-109.8%.
Keywords: Green Chemistry Technology; Solid Phase Extraction; herbicidy; arylsulfonany; Hydrogen-Ion Concentration; Reproducibility of Results; Calibration; Water Pollutants; sulfonylmočovinové sloučeniny; Sulfonylurea Compounds; fluorescenční spektrometrie; voda; Light; kalibrace; reprodukovatelnost výsledků; limita detekce; Water; Photochemistry; Arylsulfonates; látky znečišťující vodu; technologie zelené chemie; extrakce na pevné fázi; fotochemie; fotolýza; Limit of Detection; světlo; Spectrometry, Fluorescence; koncentrace vodíkových iontů; Herbicides; Photolysis